Transformation of the Awareness of Prospective Married Couples through Premarital Guidance: A Philosophical Perspective of the Sukamulya Religious Affairs Office - Reza Fahlevi Nurpaiz; Novia Nurul Izzati; Aspandi Aspandi; Rafiudin Rafiudin; Bidayatul Inayah (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2025)
This study aims to analyze the implementation of the premarital guidance program at the Sukamulya District Religious Affairs Office (KUA) and assess its contribution to fostering harmonious families. The study also identifies supporting factors, inhibiting factors, and the program's impact on the readiness of prospective brides and grooms. This study is crucial due to the high number of cases of household disharmony and the need to evaluate the effectiveness of premarital guidance as a preventative measure. Academically, this study addresses the lack of empirical studies related to the implementation and effectiveness of premarital guidance at the sub-district level, including the gap between the material provided and family practices after marriage. Using qualitative field research methods, data were collected through observation, interviews, and documentation. The results indicate that the implementation of guidance includes education on marital values, conflict management, and financial management.. Supporting factors included institutional support, participant enthusiasm, comprehensive materials, and competent resource persons. Inhibiting factors included time constraints, lack of active participation, accessibility constraints, and minimal post-counseling evaluation and support. Visible impacts included improved understanding of prospective brides and grooms, mental-emotional readiness, and the quality of couple communication. However, long-term effectiveness remains uncertain due to the lack of follow-up monitoring. This study confirms that premarital counseling plays a crucial role in building harmonious families, but requires strengthening interactive methods and ongoing evaluation.